Experimental study on the bonding performance of stainless-steel reinforcement and seawater-sea sand concrete under simulated marine environment - Ran Li; Ruirui Zhang; Baofeng Zheng; Zhongzheng Guan; Haiyun Li (Case Studies in Construction Materials, 2025)
To study the bonding performance (BP) of stainless-steel reinforcement (SSR) and seawater-sea sand concrete (SSC) before and after corrosion, 12 groups of stainless-steel reinforcement and seawater-sea sand concrete (SSR-SSC) center-drawing specimens and 1 group of HRB500 carbon steel seawater-sea sand concrete (CS-SSC) specimens were designed and fabricated to perform accelerated corrosion and center drawing tests, and each group contained 3 samples, totaling 39 samples. The damage mode of the specimens after corrosion was dominated by splitting failure (SF), while pull-out failure (PF) and pull-out-splitting failure (PSF) also occurred in some specimens during the tests. The analysis results reveal that the voids of the concrete specimens were filled by the corrosion products. The increase of the corrosion temperature resulted in the accumulation of more corrosion products, which induced the additional microcracking in the concrete specimens. This microcracking progressively reduced the ultrasonic velocity. It was also found that a larger relative thickness of the concrete cover can improve how effectively the concrete restrains the reinforcement, with the improvement reaching as high as 71.74 %. Furthermore, the ultimate pull-out load of the specimens was found to improve by increasing the relative anchorage length within a specific range, achieving a peak increase of 43.95 %. However, as the contact area between the steel bar and the concrete increased, the bond stress decreased, with a maximum reduction of 53.51 %. Based on the test results, a formula for the calculation of the bond strength of SSR-SSC is proposed, and its high accuracy is verified by the results of a comparative analysis.